Capturing the built environment-travel interaction for strategic planning: Development of a multimodal travel module for the Regional Strategic Planning Model (RSPM) - Liming Wang; Brian Gregor; Huajie Yang; Tara Weidner; Tony Knudson (Journal of Transport and Land Use)
Integrated land use and transportation models have evolved along a spectrum from simple sketch planning models to complex microsimulation models. While each has its niche, they are largely unable to balance the flexibility and realism of microsimulation and the speed and interactivity of simple models. The Regional Strategic Planning Model (RSPM) aims to fill this gap by taking a microsimulation approach while making other simplifications in order to model first-order effects quickly. It enables planners to consider the robustness of prospective policies in the face of future uncertainties by accepting a broad range of inputs and allowing rapid simulations of many scenarios.